Effect of catalyst and temperature on the quality and productivity of HTL bio-oil from microalgae: A review. (August 2021) - Sharma, Nishesh; Jaiswal, Krishna Kumar; Kumar, Vinod; Vlaskin, Mikhail S.; Nanda, Manisha; Rautela, Indra; Tomar, Mahipal Singh; Ahmad, Waseem
Abstract: Algae biomass has been recognized as one of the most suitable, efficient, and reliable feedstocks for bio-oil production. Among the different processes, hydrothermal liquefaction (HTL) is emerging as an effective technology for the valorization of various types of wet or dry biomass. Several factors, including temperature, retention time, and catalyst, significantly influence the overall efficiency of HTL products. The temperature ∼280 ± 40 °C is reported to be the most suitable range to achieve maximum bio-oil. Both homogeneous and heterogeneous catalysts have been used to improve bio-oil yield. For several advantages, heterogeneous catalysts are the preferred choice due to improved bio-oil generation, easy recovery, and uses. The eco-friendly approach and the reduction of heteroatoms in bio-oils make heterogeneous catalysts an ideal choice to be fortified. Alkaline catalysts have been considered most suitable to improve HTL yield. Variations in temperature and catalysts not only influence the yield of the bio-oil but also influence the characteristics of the bio-oil (e.g. high heating value, oxidative stability, gaseous emission, etc.) simultaneously. This review reveals interesting features including HTL temperature vs. yield, catalysts vs. yield, and the effect of wet and dry biomass on bio-oil properties, and finally, observations, remarks/limitations are presented for future studies. Highlights: HTL process as an energy-efficient thermochemical conversion for microalgae biomass. HTL bio-oils from wet and dry algal biomass under various process parameters. Process mechanism and product yield under the influence of catalyst and temperature. Impact of homogeneous and heterogeneous catalysts on HTL product (bio-oils). Alkaline catalysts in hydrothermal liquefaction to improve the yield of bio-oils.